Legally enforceable smart contract wills - Chua, Kelvin Chong Hung (Nanyang Technological University, 2023)
Blockchain Technology have the potential to radically alter the way that people have executed wills for centuries. Traditional wills are usually written down onto a piece of paper to divide your assets according to your wishes to your beneficiaries. This project explores the method of harnessing the blockchain technology such as Ethereum to create a distributed ledger of wills to maintain a reliable record of a testator desirers. By using blockchain technology with the innovations of the best aspects of electronic wills, a blockchain will could serve as a reliable, authentic, and secure record of a decedent's last wishes for disposition of her property.